PERUBAHAN BUDAYAORGANISASI DAN PENGARUHNYATERHADAPKINERJAKARYAWAN : SUATU TINJAUAN PUSTAKA - Andarias Patiran (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2007)
The aim of this written article is to know and explain the conceptual work plan of the organization culture to the employees service in a organization.The culture change which happens in a organization flows and appears in a movement, conflic, or bump, but its not a frightened thing.A change is needed, even in a little scale. It shows that there is a life in an organization, if the change is managed well and consistently by regarding the man power will product the development and increase the employees service in a organization